Pengembangan Model Sosial-Ekonomi Penanganan Stunting di Kabupaten Aceh Timur - Andiny, Puti; Junita, Afrah; Meutia, Tuti; Salman, Salman (Jurnal Samudra Ekonomi dan Bisnis, 2024)
East Aceh District is one of the areas that has a high stunting prevalence rate/above the Aceh Provincial average of 33,5 percent. This means that, according to WHO, East Aceh District has a poor public health problem or a chronic stunting problem. The purpose of this study was to identify the socio-economic determinants of stunting and formulate an alternative model for handling stunting in East Aceh District. This research used a qualitative approach, whit primary data sources through FDGs and interviews with relevant agencies. After obtaining result about the determinants of stunting, an analysis was carried out using the SWOT method to obtain an alternative model. The results of the study obtained that the dominant factor causing stunting is the family economy and the alternative handling model is through empowering village communities in meeting food needs independently.